Effective magnetic monopole mechanism for localized electron pairing in HTS - Diamantini, M. C.; Trugenberger, C. A.; Vinokur, V. M. (Frontiers in Physics, 2022)
The mechanism responsible for spatially localized red strong coupling electron pairing characteristic of high-temperature superconductors (HTS) remains elusive and is a subject of hot debate. Here, we propose a new HTS pairing mechanism which is the binding of two electrons residing in adjacent conducting planes of layered HTS materials by effective magnetic monopoles forming between these planes. The pairs localized near the monopoles form real-space seeds for superconducting droplets, and strong coupling is due to the topological Dirac quantization condition. The pairing occurs well above the superconducting transition temperature T_c. Localized electron pairing around effective monopoles